Whole‐Cell Biotransformation of Penicillin G by a Three‐Enzyme Co‐expression System with Engineered Deacetoxycephalosporin C Synthase. (20th April 2022) - Song, Shiyi; Jiang, Yingying; Chen, Ruidong; Su, Wencheng; Liang, Weinan; Yang, Dameng; Li, Jincheng; Zhang, Wuyuan; Gao, Shushan; Yuan, Bo; Qu, Ge; Sun, Zhoutong
Abstract: Deacetoxycephalosporin C synthase (DAOCS) catalyzes the transformation of penicillin G to phenylacetyl‐7‐aminodeacetoxycephalosporanic acid (G‐7‐ADCA) for which it depends on 2‐oxoglutarate (2OG) as co‐substrate. However, the low activity of DAOCS and the expense of 2OG restricts its practical applications in the production of G‐7‐ADCA. Herein, a rational design campaign was performed on a DAOCS from Streptomyces clavuligerus (scDAOCS) in the quest to construct novel expandases. The resulting mutants showed 25∼58 % increase in activity compared to the template. The dominant DAOCS variants were then embedded into a three‐enzyme co‐expression system, consisting of a catalase and an L‐glutamic oxidase for the generation of 2OG, to convert penicillin G to G‐7‐ADCA in E. coli . The engineered whole‐cell enzyme cascade was applied to an up‐scaled reaction, exhibiting a yield of G‐7‐ADCA up to 39.21 mM (14.6 g ⋅ L −1 ) with a conversion of 78.42 mol %. This work highlights the potential of the integrated whole‐cell system that may inspire further research on green and efficient production of 7‐ADCA. Abstract : Deacetoxycephalosporin C synthase (DAOCS) requires 2‐oxoglutarate (2OG) as a co‐substrate to catalyze the conversion of penicillin G to phenylacetyl‐7‐aminodeacetoxycephalosporin acid (G‐7‐ADCA). Catalase and L‐GOX were introduced into the catalytic process of ring expansion to construct a 2OG production module to form a three‐enzyme co‐expression system, so as to realize the conversion of penicillin G to G‐7‐ADCA in vivo .